Existent state and removal rate of silver in lead-silver slag during the melt-vaporization process - Shen Y.-Y.; Zhao X.-S.; Zhang F.-J.; Ma W.-X.; Wang X.-F.; Du X.-Y. (Journal of Mining and Metallurgy. Section B: Metallurgy)
In this paper, Ag contained in the lead-silver slag was recovered during the melt-vaporization process. The existing Ag state in the soot was analyzed, the influence of the reaction temperature, the carbon ratio, and the reaction time on the removal rate of the silver was investigated, and the process conditions were optimized using reaction surface methodology. Silver chloride, silver metal, silver sulfide, silver oxide, and silver sulfate are the main silver phases in lead-silver slag, of which silver chloride and silver sulfide are the main phases. The silver oxide (Ag2O) and the silver chloride (AgCl) in the leadsilver slag volatilize to soot, the silver sulfide (Ag2S) is oxidized by oxygen to silver sulfate (Ag2SO4), and elemental silver volatilizes with Pb and Zn to form alloys. The silver is ultimately present as Ag, AgCl, Ag2O and Ag2SO4 in the soot. The removal rate of the silver gradually increases with increasing reaction temperature and tends to remain stable at 1300°C. With a gradual increase in the carbon content, the removal rate of silver first increases and then decreases. The highest value is 80.12 wt% when the carbon content is 16.30 wt%. As the holding time increases, the silver removal rate gradually increases and then stabilizes at 79.97 wt% even at a holding time of 150 minutes. The optimum process conditions for silver removal are a reaction temperature of 1340°C, a carbon content of 16.10 wt%, and a holding time of 165 minutes. The average removal rate of silver under these conditions is 80.42 wt%. The research in this article provides a theoretical basis for the removal and utilization of silver from lead and silver residues.